THE KARAMKEN GOLD-SILVER DEPOSIT (MAGADAN OBLAST, RUSSIA): MINERALOGICAL AND GEOCHEMICAL CHARACTERISTICS AND THE METAL DISTRIBUTION PATTERN IN THE GLAVNAYA VEIN - Bryzgalov I.A. (My University, 2001)
Chemical compositions of Au, Ag, and Sn minerals have been studied with the help of detailed electron microprobe analyses. The sequence of their crystallization has been defined more precisely. Distribution maps of native gold and native silver, sulfostannates, tetrahedrite-tennantite minerals, silver selenides and tellurides, Ag-Sb sulfosalts, and acantite in a vertical section of the vein were compiled. The ore body is shown to have formed during two mineralization stages: (1) the cassiterite-sulfide stage, and (2) the gold-silver stage. The mineral aggregates crystallized during these stages are spatially overprinted. The bonanza distribution of ores and the mosaic-block zonality of a stadial and facies nature resulted from this phenomenon. On the basis of a paragenetic study of mineral assemblages, the variability of the physicochemical environment has been established.